The Use of Sign Language in Deaf Indonesian Classrooms in Surakarta - Isnaniah, Siti; Agustina, Tiya; Islahuddin; Annisa, Faqih (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Sign language is the language used by the deaf to communicate. In general, there are two types of sign languages used in Indonesia, namely SIBI (Indonesian sign language system) and BISINDO (Indonesian sign language). Of the two, the sign language most often used by the deaf is BISINDO, because BISINDO is considered easier to understand. This study aims to explain the use of BISINDO in Deaf Indonesian language classes in the Surakarta Gerkatin organization. The method used in this study is descriptive qualitative with data in the form of image documentation. The data source is in the form of sign language learning process. Data collection techniques are carried out through observation, recording and note-taking techniques. Data analysis techniques use interactive models. The results showed that the movements used in BISINDO learning at Gerkatin Surakarta involved the use of facial expressions, body language, arms and hands. There is a lot of vocabulary taught such as learning words, Indonesian, not yet, like, where, like, small, eat, alone, understand, don't know, work, sleep, words, healthy, black, fat, thin, color, about, purpose, lesson, early. If you look closely at the vocabulary taught, it has different conceptual sign languages. Like a like sign, demonstrated with the position of the hands in front of the mouth, then the palms open up plus the movement of the hands sticking from the chest towards the other person. Small gesture, in front of the chest with the tip of the thumb against the ring finger and the other three fingers open upwards, accompanied by a plucking motion of the two attached fingers. All the movements taught are made natural so that they are easy to understand according to the interpretation of the deaf. Thus, it is hoped that this variation of BISINDO's sign language will be increasingly recognized and widely used in teaching deaf sign language.